1997
DOI: 10.1111/j.1540-6261.1997.tb02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Winner‐Loser Reversals in National Stock Market Indices: Can They be Explained?

Abstract: This article examines possible explanations for “winner‐loser reversals” in the national stock market indices of 16 countries. There is no evidence that loser countries are riskier than winner countries either in terms of standard deviations, covariance with the world market or other risk factors, or performance in adverse economic states of the world. While there is evidence that small markets are subject to larger reversals than large markets, perhaps due to some form of market imperfection, the reversals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
140
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(158 citation statements)
references
References 32 publications
15
140
1
2
Order By: Relevance
“…However, using the three-factor model makes the contrarian profits disappear indicating that this model fully explains these profits. Using index data of 16 countries, Richards (1997) showed that the excess returns of the loser portfolio do not reward taking an additional risk, as the latter is measured by the standard deviation of returns, the covariance with risk factors such as the world index and the exchange rate risk, or the performance of losers in various states of the world.…”
Section: The Rational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using the three-factor model makes the contrarian profits disappear indicating that this model fully explains these profits. Using index data of 16 countries, Richards (1997) showed that the excess returns of the loser portfolio do not reward taking an additional risk, as the latter is measured by the standard deviation of returns, the covariance with risk factors such as the world index and the exchange rate risk, or the performance of losers in various states of the world.…”
Section: The Rational Approachmentioning
confidence: 99%
“…De Bondt & Thaler, 1985Richards, 1997;Balvers, Wu, & Gilliland, 2000, Chou, Chung, & Wei, 2007Akarim & Sevim, 2013), a negative return autocorrelation (e.g. Fama & French, 1988, Bali, Demirtas, & Levy, 2008Mukherji, 2011) and a cointegration relationship between the stock prices and their fundamental value (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of other studies have essentially confirmed the prevalence of momentum effects in several segments of the international equity markets; examples include Rouwenhorst (1998;1999) for Europe and several emerging markets, as well as Chui et al (2003) for a number of Asian countries. For stock market indexes and exchange trade funds, rather than individual shares, significant momentum effects have been reported, inter alia, by Asness et al (1996); Richards (1997);Chan et al (2000) and Tse (2015) among others.…”
Section: Background and Literature Reviewmentioning
confidence: 97%
“…The evidence of stock-level return reversal has been mirrored in market-level studies. Evidence that international equity market indices also exhibit long-term return reversal has been reported in a number of studies, including Richards (1997), Balvers, Wu and Gilliland (2000), and Malin and Bornholt (2013). An important difference between the results from market-level studies and those from stock-level studies is that popular asset-pricing models such as the Fama-French three-factor model are unable to explain the long-term reversal in international market indices.…”
Section: Related Literaturesmentioning
confidence: 99%